Substitusi Mie Sumber Zat Gizi Mikro Bahan Pangan Lokal Lahan Gambut terhadap Daya Terima Balita Underweight Umur 24-59 Bulan: Substitution of Noodles as a Source of Micronutrients for Local Peatland Food Ingredients on the Acceptability of Underweight Toddlers Age 24-59 Months - Dahliansyah Dahliansyah; Didik Hariyadi; Desi Desi (Jurnal Surya Medika (JSM), 2022)
Nutritional problems are still a serious impact on the quality of human resources in Indonesia, especially the problem of double nutrition in children under five. Underweight is one of the serious nutritional problems that need to be addressed in addition to stunting. The handling of undernourished children under five is done by providing additional food (PMT). One of the local ingredients that can be made is dry noodles, which are high in micronutrients. Making noodles can be modified from local ingredients, including yellow sweet potato where sweet potato (Ipomoea batatas L) is a type of tuber that has many advantages. Noodles can be enriched with nutrients by adding micronutrients sourced from local peatlands, namely snakehead fish and red ferns. Snakehead fish has a protein content of 25.2%, and contains albumin 62.24 g/kg (6.22%). While the red fern contains the minerals Calcium and Iron 291.32 mg per 100 mg of material, allowing it to prevent anemia. This study aims to determine the Substitution of Noodles Source of Micronutrients Local Food Ingredients on Peat Land on Nutritional Quality and Acceptability of Underweight Toddlers Age 24-59 Months in the District of Rasau Jaya. The design of this research is pure experimental (true experiment. The number of panelists is 30 people. Statistical test using Friedman statistical test to analyze the differences in substitution of yellow sweet potato, snakehead fish and red fern on organoleptic quality (color, taste, aroma, and texture). Test results acceptability based on the average amount according to color, aroma, taste, and texture on dry noodles as a whole obtained the highest results in treatment 1, namely F1 with a total of 451. The best value was obtained in treatment P1, where the best treatment was the treatment with the highest NP value, namely P1 of 0.78 with the following characteristics: color 3.83 (somewhat like), aroma 3.97 (somewhat like), taste 3.53 (somewhat like), texture 3.53 (somewhat like), Like) Friedman test results showed that there was no effect of the addition of yellow sweet potato, snakehead fish extraction and red fern extraction on d I accept the color, taste, aroma and texture of dry noodles.